Pengaruh Kepemimpinan Guru dan Ketrampilan Manajemen Kelas Terhadap Perilaku Belajar Siswa di SDI Islam 01 YMI Wonopringgo - Ismiati, Nur; Mustakim, Zaenal; Zuhri, Saefudin; Mahmudah, Umi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2021)
One manifestation of teacher leadership is the existence of classroom management. For this reason, if teacher leadership is associated with teacher skills in classroom management, there is a very close relationship. The higher the quality of classroom management, the better the teacher’s leadership. Then further in a learning process in the classroom, it is expected to be able to create positive behavior when students are participating in learning activities. But in reality forming positive behavior when student are taking part in learning is not easy, it is necessary to have quality leadership and be accompained managment skills.the purpose of this study was to determine the effect of teacher ledership and classroom management skills on student learning behavior. Based on the result of the multiple linear based on the result of the multiple linear regression equation test conducted by the researcher, it can be concluded that teacher leadership and classroom management skills have an influence on student behavior. This is evidenced by the acquisition of the calculated F value 32,075 > F table 4,02